PEREMPUAN MINANGKABAU DALAM PANGGUNG POLITIK - Lindayanti, Lindayanti (MOZAIK Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
Women in the Minangkabau indigenous community structure have a unique role. In the Minangkabau matrilineal custom system, women are placed in a central position. Minangkabau women have been portrayed as having played a role in the political arena in Minangkabau for a long time. This can be seen from classic Minangkabau stories such as kaba, tambo or myth. Many stories of women’s heroism are found. What is the relationship between the ideal level and reality in the politics of Minangkabau women? For example, "Keagungan Bundo Kanduang" depicted in the story of Cindur Mato from an ideal level coupled with Minangkabau women performing in various fields such as Putri Rahmah el Yunusiyah also established several other women’s schools as an effort to increase the education level of women in Minangkabau.